Reduction of Structural Vibrations by Passive and Semiactively Controlled Friction Dampers - L. Gaul; J. Becker (Shock and Vibration)
Reduction of structural vibrations is of major interest in mechanical engineering for lowering sound emission of vibrating structures, improving accuracy of machines, and increasing structure durability. Besides optimization of the mechanical design or various types of passive damping treatments, active structural vibration control concepts are efficient means to reduce unwanted vibrations. In this contribution, two different semiactive control concepts for vibration reduction are proposed that adapt to the normal force of attached friction dampers. Thereby, semiactive control concepts generally possess the advantage over active control in that the closed loop is intrinsically stable and that less energy is required for the actuation than in active control. In the chosen experimental implementation, a piezoelectric stack actuator is used to apply adjustable normal forces between a structure and an attached friction damper. Simulation and experimental results of a benchmark structure with passive and semiactively controlled friction dampers are compared for stationary narrowband excitation. For simulations of the control performance, transient simulations must be employed to predict the achieved vibration damping. It is well known that transient simulation of systems with friction and normal contact requires excessive computational power due to the nonlinear constitutive laws and the high contact stiffnesses involved. However, commercial finite-element codes do not allow simulating feedback control in a general way. As a remedy, a special simulation framework is developed which allows efficiently modeling interfaces with friction and normal contact by appropriate constitutive laws which are implemented by contact elements in a finite-element model. Furthermore, special model reduction techniques using a substructuring approach are employed for faster simulation.